1981
DOI: 10.1243/jmes_jour_1981_023_028_02
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Diffuser/Rotor Interaction in a Centrifugal Compressor

Abstract: Experimental flow data recorded on a low speed centrifugal compressor rig are compared with theoretical predictions of the diffuser field. Results for four diffuser geometries are presented covering variation of the blade number, stagger angle, and radial separation of the rotor and diffuser. The theoretical predictions are based on an extension of the Martensen surface singularity theory. The diffuser is found to play a major role in establishing the circumferential variation in the mean flow at impeller out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…This lends credibility to the belieff that the vaned diffuser increases performance by affecting the aft impeller and vaneless space flewfields (Fisher and Inoue, 1981), thereby reducing secondary flows and separation. Thus, if a vaned diffuser is utilized to increase efficiency, the vane stagger should be equal to the absolute flow angle at the operating point, minimizing the loading.…”
Section: Diffuser Vane Steady Loadingsupporting
confidence: 66%
See 3 more Smart Citations
“…This lends credibility to the belieff that the vaned diffuser increases performance by affecting the aft impeller and vaneless space flewfields (Fisher and Inoue, 1981), thereby reducing secondary flows and separation. Thus, if a vaned diffuser is utilized to increase efficiency, the vane stagger should be equal to the absolute flow angle at the operating point, minimizing the loading.…”
Section: Diffuser Vane Steady Loadingsupporting
confidence: 66%
“…Optimum values given range from 1.1 to 1.15 (Rodgers, 1982;Bammert et al, 1983;Fisher and Inoue, 1981;Inoue and Cumpsty, 1984). It is generally concluded in the literature that vaned diffusers become less effective at larger radius ratios.…”
Section: Basic Theory Of Radial Diffusersmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the fluid near the low pressure side of the blade had higher velocity. Fisher and Inoue (1981) experimentally studied the interaction between the impeller and four different radial diffusers. Their results showed that the radial diffuser played a major role in establishing the circumferential variation in the mean flow at the outlet of the impeller.…”
Section: Air Entering the Fan Impellermentioning
confidence: 99%